From home to the screen: How parental rejection fuels cyberbullying in college students. - Shuaijie Lan; Yangan Wang; Jiaxu Zhao; Xujing Hou; Chao Li (PLoS ONE)
Previous research has highlighted the impact of family environment on college students' cyberbullying behavior, yet the role of parenting styles, particularly negative ones, remains underexplored. This study, grounded in the interpersonal acceptance-rejection theory and social information processing model, investigates how parental rejection influences cyberbullying behavior among college students through cognitive and emotional mechanisms. We surveyed 1,567 college students (620 males, 947 females; average age: 19.34 ± 1.24 years) from several universities in Shandong and Jilin provinces, China. Participants completed questionnaires assessing cyberbullying, parental rejection, empathy, and moral disengagement. The findings reveal that 456 individuals (29.1%) had engaged in at least one instance of cyberbullying behavior, including 180 males and 276 females. Subsequently, an investigation into the cyberbullying behaviors of these individuals revealed that: (1) parental rejection is a significant predictor of cyberbullying behavior; (2) empathy and moral disengagement serve as partial mediators in the relationship between parental rejection and cyberbullying; (3) both empathy and moral disengagement act as sequential mediators in this relationship. These results underscore the importance of empathy and moral disengagement in understanding the link between parental rejection and cyberbullying among college students, offering a new theoretical perspective for future interventions.